The complete sequence of the mitochondrial genome of Dahuabai pig (SusScrofa). (3rd May 2016) - Mao-Liang, Ran; He, Jun; Yang, An-Qi; Li, Zhi; Dong, Lian-Hua; Chen, Bin
Abstract: Dahuabai pig is one of the most important indigenous breed of the Guangzhou province of China. It is the first time that the complete mitochondrial genome sequence of Dahuabai pig is reported in this work, which is determined through the PCR-based method. The total length of the mitognome is 16, 709 bp, which contains a control region (D-loop region), 2 ribosomal RNA genes, 13 protein-coding genes and 22 tRNA genes. The total base composition of Dahuabai pig mitochondrial genome is 34.68% for A, 26.20% for C, 25.81% for T and 13.32% for G, in the order A > C > T > G. The complete mitochondrial genome of Dahuabai pig provides an important data in studying mitochondrial DNA's role in the process of metabolism and programmed cell death.